Development and psychometric analysis of the student–teacher relationship scale – short form - Settanni, Michele; Longobardi, Claudio; Sclavo, Erica; Fraire, Michela; Prino, Laura E. (Frontiers in Psychology, 2015)
The purpose of this study is the construction and validation of an Italian Short Form version of the Student-Teacher Relationship Scale (Pianta 2001; STRS-SF) in the Italian educational setting for 1256 Students and 210 teachers. The STRS-SF is a self-report measure assessing teacher perceptions of the quality of their relationship with students from grade 3 to grade 8. The items were selected from the original Italian adaptation of the regular STRS through Rasch analysis, which allowed us to identify a subset of items with proven psychometric properties. The STRS-SF consists of two subscales: Conflict (8 items) and Closeness (6 items). Results indicate that the 14-item short form can be used as a viable substitute for the regular STRS.